PENGARUH LITERASI KEUANGAN, GAYA HIDUP, DAN KEMAMPUAN AKADEMIK TERHADAP PENGELOLAAN KEUANGAN MAHASISWA DENGAN FINANCIAL ATTITUDE SEBAGAI VARIABEL MEDIASI - Septiani, Putri; helmi, sulaiman (JURNAL ILMIAH EDUNOMIKA, 2025)
This research highlights the importance of student financial management which is influenced by financial literacy, lifestyle, and academic ability, with financial attitude as mediation. Using a quantitative method based on SEM-PLS in undergraduate students, the results of the study show that financial literacy and academic ability have a significant effect on financial management through financial attitude, while consumptive lifestyles tend to be weakening. It is recommended that students improve their literacy and positive financial attitudes and control their lifestyle, while universities can support through financial education programs. The limitation of the study lies in the sample that only includes Bina Darma University.